Florid cement-osseous dysplasia of maxilla and mandible: a rare clinical case - Chandramani B. More; Rajan Shirolkar; Mansi N. Tailor (Universidade Estadual de Campinas, 2015)
Cemento-osseous dysplasia is a group of disorders known to originate from periodontal ligament tissues. Florid cemento-osseous dysplasia clearly appears to be a form of bone and/or cementoid tissues restricted to jaw bones. This lesion is usually asymptomatic and is incidentally detected during routine radiographic examination. The diagnosis is made by clinical and radiographic examinations, and biopsy is not necessary. The patient must manifest the typical changes in at least two quadrants. An asymptomatic individual requires only a periodic follow-up to ensure that there is no change in the disease behavior. Surgical management is indicated only for a progressive lesion that produces orofacial disfigurement. This paper presents a rare case of a 60-year-old female who was clinically and radiographically diagnosed as having florid cemento-osseous dysplasia in the maxilla and mandible. Discussion is presented with emphasis on clinical and radiographic manifestations.